Prospective solvency in ensuring the financial stability of the enterprise - Vita Vynogradnya (Hryhorii Skovoroda University in Pereiaslav, 2021)
Issues of ensuring the financial stability of enterprises are extremely important for the socio-economic development of Ukraine. Stable operation of the enterprise is possible only if the appropriate level of solvency of the enterprise. That is why the issues and problems related to ensuring solvency are given much attention in the scientific works of scientists from both foreign and domestic scientific schools. At the same time, insufficient attention is paid to long-term solvency as an important component of the system of ensuring the stable functioning and development of the enterprise in the future. The task of the study is to analyze the approaches of scientists to the interpretation of the essence of prospective solvency and its role in ensuring the stable operation of the enterprise, determining the characteristic causes of its decline in modern socio-economic development of Ukraine; development of a proposal to ensure the solvency of the enterprise in the future. In the process of research general and special methods were used: analysis and synthesis, method of comparison, generalization, statistical, etc. The article considers the essence of perspective solvency of the enterprise and its role in ensuring stable functioning of the enterprise. The factors that determine it are systematized. The conceptual model of providing perspective solvency of the enterprise for the purpose of stable functioning and development of the enterprise which provides: definition of a system of the corresponding indicators of perspective solvency for their constant monitoring is offered; finding out the possible reasons, which may result in loss of prospective solvency; the sequence of implementation of the necessary measures for its restoration and provision in the future. The results of this study can be used in the process of enterprise management to determine the real state of its solvency and develop measures to ensure it in the medium and long term.